Characterization of nuclear structures containing superhelical DNA. - Cook, P; Brazell, I; Jost, E (1976)
Structures resembling nuclei but depleted of protein may be released by gently lysing cells in solutions containing non-ionic detergents and high concentrations of salt. These nucleoids sediment in gradients containing intercalating agents in a manner characteristic of DNA that is intact, supercoiled and circular. The concentration of salt present during isolation of human nucleoids affects their protein content. When made in I-95 M NaCl they lack histones and most of the proteins characteristic of chromatin; in 1-0 M NaCl they contain variable amounts of histones. The effects of various treatments on nucleoid integrity were investigated.